Definition and management of odontogenic maxillary sinusitis - Soung Min Kim (SpringerOpen, 2019)
Abstract Background Maxillary sinusitis of odontogenic origin, also known as maxillary sinusitis of dental origin or odontogenic maxillary sinusitis (OMS), is a common disease in dental, otorhinolaryngologic, allergic, general, and maxillofacial contexts. Despite being a well-known disease entity, many cases are referred to otorhinolaryngologists by both doctors and dentists. Thus, early detection and initial diagnosis often fail to detect its odontogenic origin. Main body We searched recent databases including MEDLINE (PubMed), Embase, and the Cochrane Library using keyword combinations of "odontogenic," "odontogenic infection," "dental origin," "tooth origin," "sinusitis," "maxillary sinus," "maxillary sinusitis," "odontogenic maxillary sinusitis," "Caldwell Luc Procedure (CLP)," "rhinosinusitis," "functional endoscopic sinus surgery (FESS)," "modified endoscopy-assisted maxillary sinus surgery (MESS)," and "paranasal sinus." Aside from the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) trial, there have been very few randomized controlled trials examining OMS. We summarized the resulting data based on our diverse clinical experiences. Conclusion To promote the most efficient and accurate management of OMS, this article summarizes the clinical features of rhinosinusitis compared with OMS and the pathogenesis, microbiology, diagnosis, and results of prompt consolidated management of OMS that prevent anticipated complications. The true origin of odontogenic infections is also reviewed.